Memadukan Pendakian dan Wisata Edukasi: Persoalan Gunung Api dan Geopark Batur di Kawasan Kintamani, Bali - I Gede Mudana; I Ketut Sutama; Cokorda Istri Sri Widhari (Universitas Udayana, 2018)
The Batur volcano in Kintamani tourist resort has enhanced its existence through the establishment of Batur UNESCO Global Geopark since 1st April 2016. However, the two tourist attrac- tions have not been mutually utilized each other. This study is conducted to determine the level of relationship and integra- tion between the two tourist attractions in order to find out beneficial solution for the two tourism industries. The results revealed that not all tourists’ climbers of Mount Batur visited the Geopark as an artificial-tourist attraction, whereas, not all the first tourists who visited the geopark was climbing the sa- cred mountain. Therefore, it is required more intensive efforts in tourism business in order to create a mutual synergy be- tween the two tourist attractions by all stakeholders including government, tourism industry, and the society. This is for the benefit of tourism business and of carrying out the natural con- servation and the preservation of local cultural values.